Epithrix hirtipennis, a New Pest of Tobacco in Greece, with Notes on its Morphology, Bioecology and Control - Lykouressis, D.P. (ENTOMOLOGIA HELLENICA, 1991)
The tobacco flea beetle, Epithrix hirtipennis (Melsheimer) (Coleoptera: Chrysomelidae) was first noticed on tobacco in Agrinio area in early May 1988. In the next year it was also found to attack tobacco in the same area. Heavy attacks were also recorded on eggplant while a low infestation was noticed on potato and pepper. To date this species is widespread in several areas of Phthiotis (Central Greece) where tobacco is grown developing quite large populations. The adult feeds on the leaves causing almost circular holes, usually 1-2 mm in diameter, and irregular shape ones when they are larger. The adult starts feeding usually from the upper surface of the leaves and to a lesser extent from the underside. When large numbers of adults are present, larger holes are caused on the tobacco leaves while in higher population densities, the whole lamina except of nerves can be eaten, leading to severe damage of the crop. The adult was usually found on the upper surface of the lower tobacco leaves. It showed a strong feeding preference for the lower then the upper leaves of tobacco, as well as plants of reduced growth. The latter preference could be taken into account in an integrated pest management programme for tobacco pests. E. hirtipennis is of nearctic origin, known in U.S.A., Canada, Cuba, Mexico, Guatemala, Panama, Colombia and pos sibly occurs in other areas of Central and South America. It is a polyphagous species attacking cultivated plants and weeds such as tobacco, eggplant, potato, tomato, pepper, Jimson weed, ground cherry, nightshade, horse nettle and to a lesser extent many other plants. In tobacco, one adult has been estimated that can eat leaf quantity equal to ten times of its own weight in a day. Therefore, it can lower both the quantity and quality of leaves. E. hirtipennis was unknown to European countries until 1983. The first record in Europe was on tobacco in the area of Benevento, in the Campania region, South Italy. Later, it was recorded in Toscana, whilst Sannino and Balbiani reported that it was already present in the provinces of Campania, Basilicata, Lazio, Puglia, Abruzzo, Toscana and Umbria; Toscana and Umbria are the last areas in which the species was recorded. After its appearance, it has progressively spread into South and Central Italy causing damage which depends upon tobacco type. The record of E. hirtipennis at first in Agrinio area and later in other areas of Central Greece reveals that it rather invaded West Greece through transport from Italy and has spread to other areas.